(untitled) (TAMADDUN NURI JURNALI, 2024)
In the short story “Loneliness” by U. Hamdam, a diverse image of the human psyche is expressed from different angles. In our literature, the relationship between the spirit and the event is one of the primary features of the artistic work. The achievements of prose works, especially short stories, are being evaluated by the level of mental imagery, and it seems that attention to the role of the epic narrative is waning. In particular, in realistic stories, the epic narrative is primary, while in non-traditional stories, psychological analysis takes the main place. Although these two components are related to each other, one of them dominates the image. In the story “Loneliness” by U. Hamdam, it is manifested with the priority of the psyche.